Solar Photocatalytic Degradation of Antibiotics in Wastewater by Advanced Oxidation Technology: Optimization using the Response Surface Methodology - Khudhair, Hebatallah Mohammed; Hussein, Teba Saadi; Hashim, Hawraa Jumaa; Naser, Omar Sajer; Abdulhasan, Maryam Jawad (Engineering, Technology & Applied Science Research, 2025)
Amoxicillin, a widely used antibiotic, is increasingly recognized as an environmental threat due to its persistence in aquatic ecosystems and potential risks to human health. This study investigated the removal of amoxicillin from simulated pharmaceutical wastewater using a solar-powered photocatalytic process with titanium dioxide (TiO₂) in a tube-shaped reactor. The degradation efficiency was assessed by monitoring the reduction in amoxicillin concentration under varying experimental conditions. A Box–Behnken Design (BBD) was applied to evaluate the effects of key parameters, including: initial amoxicillin concentration (10-100 mg/L), TiO2 dosage (50, 75, and 100 mg/L), hydrogen peroxide (H2O2) concentration (200-600 mg/L), and pH levels (3, 5, and 7). The results revealed an optimal degradation efficiency of 90.0% under the following conditions: pH=5, 10 mg/L of amoxicillin concentration, 75 mg/L of TiO2 dosage, and 400 mg/L of H2O2 with a 150-minute exposure to solar irradiation. Statistical analysis using Analysis of Variance (ANOVA) yielded high model accuracy, with R² = 96.59%, adjusted R² = 93.18%, and predicted R² = 81.7%, indicating strong agreement between experimental data and model predictions. The findings confirm the effectiveness of solar-driven photocatalysis in degrading amoxicillin, highlighting its potential as a cost-effective and environmentally sustainable approach for pharmaceutical wastewater treatment.